1999
DOI: 10.1109/10.764946
|View full text |Cite
|
Sign up to set email alerts
|

Parametric model derivation of transfer function for noninvasive estimation of aortic pressure by radial tonometry

Abstract: Aortic pressure can be estimated noninvasively by applying a transfer function (TF) to radial tonometry signals. This study compares the performance of prior approaches, based on Fourier transform and inverted aortic-to-radial model, with direct radial-to-aortic autoregressive exogenous (ARX) model. Simultaneous invasive aortic pressure and radial tonometry pressure were recorded during rest in 39 patients in the supine position. Individual radial-aortic TF's were estimated from 20 patients, and the average TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 17 publications
8
136
1
2
Order By: Relevance
“…Several invasive studies tested SC's GTF for cSBP estimation from radial pressure waveforms. [5][6][7][8][9] However, they calibrated radial waveforms by 'invasive' central DBP and MAP and not oscillometric arm pressures, which is how SC measurements are done in practice. Later, other invasive studies consistently showed that cSBP estimated by a GTF with 'non-invasively' calibrated radial waveforms significantly underestimated invasively measured cSBP [10][11][12] with the mean difference being 11-13 mm Hg in two studies, 10,27 7-8 mm Hg in three 11,28,29 and 1.5-4.2 mm Hg in two reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several invasive studies tested SC's GTF for cSBP estimation from radial pressure waveforms. [5][6][7][8][9] However, they calibrated radial waveforms by 'invasive' central DBP and MAP and not oscillometric arm pressures, which is how SC measurements are done in practice. Later, other invasive studies consistently showed that cSBP estimated by a GTF with 'non-invasively' calibrated radial waveforms significantly underestimated invasively measured cSBP [10][11][12] with the mean difference being 11-13 mm Hg in two studies, 10,27 7-8 mm Hg in three 11,28,29 and 1.5-4.2 mm Hg in two reports.…”
Section: Discussionmentioning
confidence: 99%
“…The GTF has been derived and tested in several invasive studies using 'invasive' calibration of radial waveform. [5][6][7][8][9] However, there is still controversy over accuracy of the typical outpatient SC measurements using 'noninvasive' calibration with brachial pressures, and in different patient populations. 4,[10][11][12][13][14] Recently, two other non-invasive devices that do not use a transfer function have been introduced for cSBP and wave reflection measurement, the Omron HEM-9000 (OM) (Omron Healthcare, Kyoto, Japan) and Arteriograph (AG) (TensioMed, Budapest, Hungary).…”
Section: Introductionmentioning
confidence: 99%
“…The authors confirm prior observations that indicate the use of a general transfer function can show a considerable amount of bias and variation that limits the utility of this approach in accurately predicting the central augmentation index. 10,11 Further support for this contention is provided by a recent study where simultaneous recordings of invasive central aortic and noninvasive radial blood pressure waveforms were made in 78 subjects. 12 Values for the augmentation index, derived using transfer functions applied to the radial waveforms, were significantly different from directly measured values, and no correlation was evident between the 2 estimates.…”
mentioning
confidence: 99%
“…15,16 The central aortic pressure can also be reconstructed from peripheral arterial pressure measurements by utilizing the transfer function between each pressure waveform. 17,18 In addition, umbilical artery catheterization often performed in critically ill neonates provides continuous monitoring of central aortic pressure (there is a close correlation between descending Ao dp/dtmax and ascending Ao dp/dtmax; descending Ao dp/dtmax = 0.91 × Ao dp/dtmax +79, R=0.93, SEE =61, n=34, unpublished data from our laboratory). Therefore, incorporating the present result of a consistent relationship between the Ao dp/dtmax/ LV dp/dtmax ratio and vascular loading properties into the noninvasively estimated central aortic pressure, together with simultaneously measurement of ascending aortic flow by echocardiography, is a novel method of noninvasive calculation of LV dp/dtmax.…”
Section: Discussionmentioning
confidence: 99%